Fenomena Perkawinan Dini Persektif Maqashid Syari’ah: (Studi Kasus Di Kecamatan Sumberjambe, Kabupaten Jember Jawa Timur) - Awaliya Safithri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2020)
Early marriage is a phenomenon that still occurs frequently, especially in communities with rural cultures. And especially in village communities that uphold religious values, as is the case in the community of Sumberjambe District, Jember Regency. Sumberjambe itself is an area in Jember Regency which is close to the forestry area and is located under the slopes of Mount Raung. The review used in this research is the maqashid sharia theory in order to obtain an objective conclusion. The aim of this research is to determine the factors behind the occurrence of early marriage in Sumberjambe District and analyze the views of religious leaders regarding early marriage from a maqashid sharia perspective. The approach used in this research is a descriptive-qualitative approach with the type of field research. And the results of this research are among the first, it was found that several factors were behind the occurrence of early marriage in Sumberjambe District, including economic factors, in this case there were several parents who wanted to immediately let go of their children in the hope of reducing the cost of living in the family. Then there is the promiscuity factor, many people think that communication using social media makes teenagers free from parental supervision, resulting in out-of-wedlock pregnancies and marriage is the solution.